Metal shape detection and evaluation using giant magneto resistance system - Misron, Norhisam; Roslan, M. K.; Aris, Ishak; Hamidon, Mohd Nizar (Universiti Putra Malaysia Press, 2017)
Visual inspection to locate metals embedded in walls or floors is impractical. Detection of these metals can only be done with a proper metal detection. Accordingly, the development of a magnetic imaging system based on giant magneto-resistance (GMR) sensors is presented for metal shape detection. This system is based on magnetic flux leakage testing (MFLT) principle for detecting the shape of ferromagnetic material specimens. The imaging system is constructed using 21 linear GMR sensors array as signals sensing unit (SSU). In this study, a few ferromagnetic SS400 mild steels specimens in various shapes are used as specimens. Image produced confirm system functionality in detecting and evaluating metal shapes.